2012
DOI: 10.1108/10444061211218294
|View full text |Cite
|
Sign up to set email alerts
|

Bridging social distance in inter‐cultural negotiations: “you” and the bi‐cultural negotiator

Abstract: Purpose-In this study of Korean and U.S. negotiators, we demonstrate limits on the presumption that inter-cultural negotiations are doomed to generate low joint gains. Design/methodology/approach-In a laboratory study with 45 bi-cultural Korean students and 47 mono-cultural American students, we created a total of 16 U.S.-U.S., 15 Korean-Korean, and 15 U.S.-Korean dyads. We audio-recorded their negotiation conversations and analyzed the content of the negotiation transcripts. We focused on the use of pronouns … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 56 publications
0
13
0
1
Order By: Relevance
“…The ability to anticipate one's counterpart's culturally normative behaviors can be critical for inter-cultural negotiation success (Lee, Adair, and Seo 2011). Negotiators who lack accurate knowledge of the counterpart's culturally normative behavior may form inaccurate interpretations of his or her behavior, which can precipitate the strategic mismatches that arise all too commonly in inter-cultural negotiations (Lee 2005;Adair, Taylor, and Tinsley 2009;Kern et al 2012). Global negotiators will benefit from knowledge of regional differences, knowledge that does not assume that a Korean partner in an upcoming negotiation will behave similarly to a Japanese partner in a previous negotiation just because both are East Asians.…”
Section: Practical Implications For Those Negotiating In East Asiamentioning
confidence: 99%
“…The ability to anticipate one's counterpart's culturally normative behaviors can be critical for inter-cultural negotiation success (Lee, Adair, and Seo 2011). Negotiators who lack accurate knowledge of the counterpart's culturally normative behavior may form inaccurate interpretations of his or her behavior, which can precipitate the strategic mismatches that arise all too commonly in inter-cultural negotiations (Lee 2005;Adair, Taylor, and Tinsley 2009;Kern et al 2012). Global negotiators will benefit from knowledge of regional differences, knowledge that does not assume that a Korean partner in an upcoming negotiation will behave similarly to a Japanese partner in a previous negotiation just because both are East Asians.…”
Section: Practical Implications For Those Negotiating In East Asiamentioning
confidence: 99%
“…Ireland and Henderson () also observed that language style matching in the initial phases of negotiations predicted more positive interactions. The importance of linguistic matching for reaching an agreement has also been demonstrated in intercultural negotiations (Kern, Lee, Aytug, & Brett, ), conflict resolution between romantic partners (Bowen, Winczewski, & Collins, ), team performance (Yilmaz, ), and interpersonal mediation (Donohue & Liang, ; Olekalns, Brett, & Donohue, ).…”
Section: Background: the Many Faces Of International Diplomatic Negotmentioning
confidence: 92%
“…Their analysis, which compares Korean and U.S. negotiators, shows that seeking priority information clusters around the use of "you" for Korean but not U.S. negotiators. Kern et al (2012) conclude that Korean negotiators use "you" to reduce the social distance between negotiators.…”
Section: Global Shadow Boxesmentioning
confidence: 95%
“…() conclude that U.S. negotiators use offers for information consolidation, whereas Japanese negotiators use offers for information gathering. Kern, Lee, Aytug, and Brett () provide a more fine‐grained analysis of strategy‐in‐context by focusing on the strategies that cluster around the pronoun “you.” Their analysis, which compares Korean and U.S. negotiators, shows that seeking priority information clusters around the use of “you” for Korean but not U.S. negotiators. Kern et al.…”
Section: Connecting Negotiation Inputs and Outputs: Illuminating The mentioning
confidence: 99%
See 1 more Smart Citation